The dynamics and dilemmas of the Niger Delta: a discourse on insecurity and demographic transition (2013)
The relative advantage of its cities blurred the inherent multidimensional consequences of oil exploration on the environment. Over time, the effects of oil spills Oil the inhabitants were massive. The people's agony was exacerbated by perceived governmental neglect which accounted for the amplification of frustration and aggression among a large majority of the poor that constitute more than three-quarters of the population. As a result, different categories of individuals became activists committed to peaceful protests. However, with a plethora of insensitive and irresponsible governments, the legitimate means soon evolved into militancy, political thuggery and assassinations. Consequently, Niger Delta communities became synonymous with insecurity, pseudo-governance and youth restiveness. This article examined the trends and dimensions of the unholy dynamics that drove demographic transition in the region by highlighting the connections between the dilemma of a failed state and underdevelopment.